Fidelity of a Bacterial DNA Polymerase in Microgravity, a Model for Human Health in Space - Rosenstein, Aaron H; Walker, Virginia K (Frontiers in Cell and Developmental Biology, 2021)
Long-term space missions will expose crew members, their cells as well as their microbiomes to prolonged periods of microgravity and ionizing radiation, environmental stressors for which almost no earth-based organisms have evolved to survive. Despite the importance of maintaining genomic integrity, the impact of these stresses on DNA polymerase-mediated replication and repair has not been fully explored. DNA polymerase fidelity and replication rates were assayed under conditions of microgravity generated by parabolic flight and compared to earth-like gravity. Upon commencement of a parabolic arc, primed synthetic single-stranded DNA was used as a template for one of two enzymes (Klenow fragment exonuclease+/-; with and without proofreading exonuclease activity, respectively) and were quenched immediately following the 20 second microgravitational period. DNA polymerase error rates were determined with an algorithm developed to identify experimental mutations. In microgravity Klenow exonuclease+ showed a median 1.1-fold per-base decrease in polymerization fidelity for base substitutions when compared to earth-like gravity (p = 0.02), but in the absence of proofreading activity, a 2.4-fold decrease was observed (p = 1.98 x 10-11). These effects were, however, less substantial when sequence-context was not considered in the analysis. Similarly, 1.1-fold and 1.5-fold increases in deletion frequencies in the presence or absence of exonuclease activity (p = 1.51 x 10-7 and p = 8.74 x 10-13), respectively, were observed in microgravity compared to controls. The development of this flexible semi-autonomous payload system coupled with genetic and bioinformatic approaches serves as a proof-of-concept for future space health research.